Pleural mesothelioma classification update - Beasley, Mary Beth; Galateau-Salle, Francoise; Dacic, Sanja (Virchows Archiv : an international journal of pathology, 2021)
The 2015 WHO classification of pleural mesotheliomas includes three major histologic subtypes—epithelioid, sarcomatoid, and biphasic. Recent genomic data has supported the need for a more granular and clinically valid classification beyond the three current subtypes. Because of tumor rarity and overlapping histologic features with other tumor types, diagnostic immunohistochemical work up is essential component in establishing the final diagnosis of mesothelioma. The use of BAP1 and CDKN2A /MTAP improves the diagnostic sensitivity of effusion specimens and are valuable in establishing the diagnosis of epithelioid mesothelioma. The major change in the forthcoming WHO classification is the inclusion of mesothelioma in situ as a diagnostic category. In this review, we discuss recently proposed changes in the histologic classification of pleural mesothelioma, differential diagnosis, and importance of ancillary diagnostic studies.